Disilicon complexes with two hexacoordinate Si atoms: Paddlewheel-shaped isomers with (CIN4)Si-Si(S4CI) and (CIN2S2)Si-Si(S2N2CI) skeletons - Wagler, Joerg; Brendler, Erica; Heine, Thomas; Zhechkov, Lyuben (Chemistry - A European Journal, 2013)
The reaction of 1-methyl-3-trimethylsilylimidazoline-2-thione with hexachlorodisilane proceeds toward substitution of four of the disilane Cl atoms during the formation of disilicon complexes with two neighboring hexacoordinate Si atoms. The N,S-bidentate methimazolide moieties adopt a buttressing role, thus forming paddlewheel-shaped complexes of the type CISi(μ-mt)4 SiCl (mt=methimazolyl). Most interestingly, three isomers (i.e., with (CIN4)Si-Si(S4Cl), (CIN3S)Si-Si(S3NCI), and (CIN2S2)Si-Si(S2N2CI) skeletons as so-called (4,0), (3,1), and cis-(2,2) paddlewheels) were detected in solution by using29Si NMR spectroscopic analysis. Two of these isomers could be isolated as crystalline solids, thus allowing their molecular structures to be analyzed by using X-ray diffraction studies. In accord with time-dependent NMR spectroscopy, computational analyses proved the cis-(2,2) isomer with a (CIN2S2)Si-Si(S2N2CI) skeleton to be the most stable. The compounds presented herein are the first examples of crystallographically evidenced disilicon complexes with two Si-Si-bonded octahedrally coordinated Si atoms and representatives of the still scarcely explored class of Si coordination compounds with sulfur donor atoms.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Hypercoordination; Isomerism; Methimazole; Silicon; Xray Diffraction